How do you find the solutions to the equation x^4-6x^3+5x^2+30x-50=0?

1 Answer
Aug 14, 2016

This quartic has roots: 3+-i and +-sqrt(5)

Explanation:

f(x) = x^4-6x^3+5x^2+30x-50

By the rational root theorem, any rational zeros of f(x) are expressible in the form p/q for integers p, q with p a divisor of the constant term -50 and q a divisor of the coefficient 1 of the leading term.

That means that the only possible rational zeros are:

+-1, +-2, +-5, +-10, +-25, +-50

None of these work. So f(x) has no rational zeros.

color(white)()
Tschirnhaus transformation

First make a linear substitution called a Tschirnhaus transformation in order to simplify the quartic:

16f(x) = 16x^4-96x^3+80x^2+480x-800

=(2x-3)^4-34(2x-3)^2+144(2x-3)-143

=t^4-34t^2+144t-143

where t = (2x-3)

Since this quartic in t is monic and has no t^3 term, it can be expressed as the product of two monic quadratics with opposite middle terms:

t^4-34t^2+144t-143

=(t^2-ax+b)(t^2+ax+c)

=t^4+(b+c-a^2)t^2+(b-c)at+bc

Equating coefficients and rearranging a little, we get:

{ (b+c = a^2-34), (b-c = 144/a), (bc = -143) :}

So we find:

(a^2-34)^2 = (b+c)^2 = (b-c)^2+4bc = 20736/a^2-572

Expanding, this becomes:

(a^2)^2-68(a^2)+1156 = 20736/((a^2))-572

Multiply through by (a^2) and rearrange a little to get:

(a^2)^3-68(a^2)^2+1728(a^2)-20736=0

By the rational roots theorem, the possible rational roots of this cubic are any factors of 20736 = 2^8*3^4

That's rather a lot to try, but there are various methods to speed up the search and eventually find a^2=36 is a zero.

Let a=6

Then:

b = 1/2(a^2-34+144/a) = 1/2(36-34+24) = 13

c = 1/2(a^2-34-144/a) = 1/2(36-34-24) = -11

Hmmm. We could have spotted that one fairly easily from the simultaneous equations by looking at possible factorings of bc =-143.

Well however we get there we now have two quadratics to solve:

0 = t^2-6t+13 = (t-3)^2 + 2^2 = (t-3-2i)(t-3+2i)

0 = t^2+6t-11 = (t+3)^2-(2sqrt(5))^2 = (t+3-2sqrt(5))(t+3+2sqrt(5))

Then x=1/2(t+3)

So we get solutions to our original quartic:

x=1/2((3+-2i)+3)=3+-i

x=1/2((-3+-2sqrt(5))+3) = +-sqrt(5)